Corporate Social Responsibility, Negative Externalities, and Financial Risk: The Case of Climate Change - Timo Busch; Nils Lehmann; Volker H. Hoffmann (Tinbergen Institute, 2012)
Certain types of corporate social responsibility (CSR) activities can generate an `insurance-like' benefit for firms (Godfrey, 2005). Thus far, this risk management hypothesis has been verified for the effects of firm-specific negative events. We argue that this insurance-like benefit of CSR-activities can be equally expected in the context of long-term developments which threaten current business models. We develop our arguments for the incremental, long-term process of internalizing negative externalities. For this, we consider the negative externalities resulting from the emission of greenhouse gases (GHG) and perform a panel analysis of a sample of 1699 firms over a period of 7 years. Our results show that firms can reduce their market-based risk by curbing their GHG-emissions. We furthermore propose an opposing effect on accounting-based risk, but do not find empirical support for this. We conclude that CSR-activities aimed at reducing a firm's exposure to specific long-term developments can be sound corporate risk management, even if such activities may not yet be profitable.
Keywords: G30; M14; L20; Q20; 330; GHG-emissions; negative externalities; financial risk; corporate social responsibility; long-term developments; Klimawandel; Externer Effekt; Corporate Social Responsibility